Evaluating pinhão conservation by using ionizing radiation and refrigeration (Bioscience Journal, 2022)
Pinhão is highly perishable due to its high water activity, being easily affected by fungi during storage and also susceptible to infestation by larvae. This seed is usually marketed in the pinhão cones itself, or bulk threshed, and packed in plastic bags, chilled or ground frozen. Pinhão conservation and industrialization techniques should be developed to promote its commercialization and consumption at other times of the year, besides the seasonal period, encouraging its sustainable production, extraction and commercialization, considering its essentially extractive character. The objective of this study was to evaluate the conservation of pinhão by the use of gamma radiation and refrigeration. The pinhões were irradiated with a cobalt–60 source at a dose rate of 1 kGy. A non-irradiated sample was used as a control. The pinhões were packed in high-density polyethylene bags and stored at ambient temperature and refrigerated at 4 ºC, during 90 days. Pinhões were evaluated for weight loss, acidity, reducing sugars, vitamin C, firmness, color, total phenolic compounds, antioxidant activity and microbiological analyzes. The isolated use of gamma radiation was not effective for the maintenance of the evaluated parameters. However, when used in conjunction with refrigerated storage, it reduced the growth of aerobic fungi, as well as mesophilic and psychrotrophic microorganisms. The isolated use of refrigeration showed a reduction in weight loss, reducing sugars and an increase in vitamin C content and antioxidant activity. Thus, to increase the benefits, we suggest evaluating higher doses of radiation as a function of the thick pinhão shell.